The Influence of Understanding, Awareness, Costs and Regulations on Business Actors' Decisions to Carry out Halal Self-Declaration Certification - Jefri, Muhammad; -, Ridhwan; Enggrani Fitri, Lucky (ILTIZAM Journal of Shariah Economics Research, 2024)
This research aims to determine the influence of Understanding Factors, Awareness Factors, Cost Factors, Regulatory Factors on the decisions of micro and small enterprises (UMK) in carrying out self-declared halal certification in Jambi City. This research was conducted on micro and small enterprises (UMK) in the Food and Beverage category who have registered for self-declared halal certification in Jambi City in 2023. The method used in this research is a quantitative method. The technique used in sampling is the purposive sampling technique. The number of samples taken was 100 respondents from a population of 515. Data collection in this research used a closed questionnaire. The data analysis technique in this research was carried out using multiple linear regression tests using the SPSS 22 Application Program. The research results showed that partially the Understanding Factor and Regulatory Factors had no influence on business actors' decisions, while the Awareness and Cost Factors had a significant effect on business actors' decisions. Simultaneously, Understanding Factors, Awareness Factors, Cost Factors, Regulatory Factors influence business actors' decisions.